Pengembangan Aplikasi Sistem Cerdas untuk Menentukan Peminatan Jurusan di Universitas Diponegoro bagi Siswa Sekolah Menengah Atas - Imaduddin Abdul Rahim; Oky Dwi Nurhayati; Kurniawan Teguh Martono (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2015)
Almost in every aspect of life, people are always faced with several options. Making the right decision will greatly affect our lives in the future. Problems in decision making are also experienced by high school students or high school who want to continue their education to a higher level, namely the University. University is a choice of formal education for high school students who will continue to the higher education. Students who wish to proceed to the University of Diponegoro University will particularly difficult because of the many options available majors. Often some high school students who have a student do not get along with their chosen majors, this course will make their declining interest in learning. As an information technology solution that exists today can be utilized to see the interest of the students so that mismatch and vacillation in the selection of majors can subtract. The purpose of making the determination of intelligent systems majors at Diponegoro University, among others, is, to develop an intelligent software that can help high school students determine the appropriate department at the University of Diponegoro. Intelligent system implements advanced tracing method or Forward Chaining to determine Diponegoro University majoring in accordance with the interests of the students. This can be done by making questions like questionnaires with a variety of options to be able to know the interests of students. Forward Chaining is a method in the form of a strategy to predict or find the solution of a problem that starts with a set of known facts, then lower the new fact that the premise is based on the rule matches the known facts. The system is made to work on a desktop base with Visual Basic programming language, and the database used is Microsoft Access. The results of testing this systems shows that all the features contained in this system can work well, and are able to provide the appropriate department recommendations, as well as ranked by passing grade and information about majors contained in Diponegoro University to the users of intelligent systems is particularly students from high school.